Development and evaluation of a sandwich ELISA method for the detection of human CD306 - Xie, Xin; Wang, ChunYan; Xie, YuanQi; Wang, Xin; Chen, GuangSheng; Yan, XingRong; Cui, JiHong; Chen, FuLin; Li, Hongmin; Jin, BoQuan (Journal of immunological methods, 2013)
CD306, also known as soluble leukocyte-associated immunoglobulin-like receptor-2 (LAIR-2), is a member of an immunoglobulin superfamily with the shared characteristic of an immunoglobulin-like C2-type domain. CD306 is speculated to be secretory and has 84% similarity with the extracellular domain of CD305, which binds to the same ligands as CD306. However, data on its distribution are absent due to the lack of an efficient method to detect it. In this study, we successfully cloned the cDNA of CD306 from the peripheral blood mononuclear cells (PBMCs) of patients with hemorrhagic fever with renal syndrome. The fusion proteins were expressed and purified, and three strains of monoclonal antibodies (mAbs) against CD306 were prepared and characterized. The sandwich ELISA for detecting CD306 was established and optimized with sensitivity up to 15pg/ml, and the assay showed high specificity for the detection of CD306. With this method, a right skewed frequency distribution of CD306 in the sera of healthy subjects was determined. The concentrations of CD306 in sera and urine were detected in patients with different diseases. Aberrantly high levels of CD306 were found in the sera of pregnant women and patients with inflammation and rheumatic heart disease and in the urine of pregnant women. Meanwhile, there was a positive correlation between CD306 and soluble CD305 expression and secretion levels in sera and urine samples from patients, and both proteins inhibited CD305-mediated immunosuppressive functions. Our results demonstrate that CD306 represents a potentially useful predictor for disease diagnosis and that the method developed has potential for clinical application. •We develop a method for detection of CD306 with sensitivity up to 15pg/ml.•Aberrant level of CD306 is exited in certain diseases.•There is a positive correlation between CD306 and soluble CD305.